George Macdonald's children's fantasies and the divine imagination - Manlove, C. N. (Colin Nicholas), 1942- (The Lutterworth Press, 2020)
"The great Victorian Christian author George MacDonald is the wellspring of the modern fantasy genre. In this book Colin Manlove offers explorations of MacDonald's eight shorter fairy tales and his longer stories At the Back of the North Wind, The Princess and the Goblin, The Wise Woman, and The Princess and Curdie. MacDonald saw the imagination as the source of fairy tales and of divine truth together. For he believed that God lives in the depths of the human mind and 'sends up from thence wonderful gifts into the light of the understanding'. This makes MacDonald that very rare thing: a writer of mystical fiction whose work can give us experience of the divine. Throughout his children's fantasy stories MacDonald is describing the human and divine imagination. In the shorter tales he shows how the imagination has different regions and depths, each able to shift into the other. With the longer stories we see the imagination in relation to other aspects of the self and to its position in the world. Here the imagination is portrayed as often embattled in relation to empiricism, egotism, and greed."--